2014
DOI: 10.2147/copd.s49621
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical impact of major comorbidities in patients with COPD

Abstract: Comorbidities are frequent in chronic obstructive pulmonary disease (COPD) and significantly impact on patients' quality of life, exacerbation frequency, and survival. There is increasing evidence that certain diseases occur in greater frequency amongst patients with COPD than in the general population, and that these comorbidities significantly impact on patient outcomes. Although the mechanisms are yet to be defined, many comorbidities likely result from the chronic inflammatory state that is present in COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
247
5
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(272 citation statements)
references
References 147 publications
(370 reference statements)
6
247
5
14
Order By: Relevance
“…Chronic obstructive pulmonary disease (COPD) is a progressive disease characterized by chronic inflammation and dysfunction of the upper airways [1,2]. The WHO estimates a current mortality rate of around 64 million people; it has been estimated that, in 2030, COPD will represent the third cause of mortality in the world [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic obstructive pulmonary disease (COPD) is a progressive disease characterized by chronic inflammation and dysfunction of the upper airways [1,2]. The WHO estimates a current mortality rate of around 64 million people; it has been estimated that, in 2030, COPD will represent the third cause of mortality in the world [1].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO estimates a current mortality rate of around 64 million people; it has been estimated that, in 2030, COPD will represent the third cause of mortality in the world [1]. Currently, the relation between comorbidities and the presence and evolution of COPD is still unclear [2]. Comorbidities such as depression, anxiety and chronic pain are commonly observed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hilde et al reported the prevalence of PHT as 5%, 27% and 53% for COPD stage II, III and IV, respectively. On the other hand, about 17% of patients with PHT were reported to have COPD [6,19].…”
Section: Epidemiologymentioning
confidence: 99%
“…The main goal of lifestyle changes according to clinical and functional status, training, drug therapy, pulmonary rehabilitation, long-term oxygen therapy, noninvasive mechanical ventilation and bronchoscopic/surgical interventions is to reduce the symptoms and future risks [1,4]. Pulmonary hypertension (PHT) which is a common complication of COPD, is determinant for the prognosis of COPD, and is estimated to be the leading fourth cause of death by 2030 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы значительно возросло число публикаций, оценивающих клинические исходы коморбидной патологии -ишемической болезни сердца (ИБС) и хронической обструктивной болезни легких (ХОБЛ) [1][2][3][4][5], имеются указания об ассоциа-ции ХОБЛ с увеличением риска смертности от сер-дечно-сосудистых причин при выполнении аорто-коронарного шунтирования (АКШ) [6,7]. В то же время остается небольшим число исследований, оценивающих эффективность и исходы чрескож-ного коронарного вмешательства (ЧКВ) у пациен-тов с сопутствующей ХОБЛ в сравнении с общей популяцией.…”
unclassified